Detection of Mechanically Recovered Poultry Meat (MRPM) in Traditional Egyptian Luncheon (Emulsion Type Sausage) - Mohamed Mai A.; Zahran Dalia A.; Kassem Gehan M.A.; Emara M.M.T.; Mansour N.M. (Polish Journal of Food and Nutrition Sciences)
Detection of MRPM in emulsion type products is a challenge facing meat industry. Where, most of meat products processors in Egypt illegally replace beef meat partially or totally with MRPM in meat products to reduce products cost. Commercial and experimentally produced emulsion type sausage (traditional Egyptian luncheon) formulated with 0, 10, 30, 50, 70, 90% MRPM instead of the meat mass and cooked to different core temperature (70, 80 and 90°C) were examined for technological properties, ash, bones, cartilage and calcium (Ca) content, in addition to histological sections stained with H&E and Trichrome blue. Results indicated that all market samples showed unacceptable texture and binding scores with high ash, collagen, cartilage, bone and Ca content. Histological section showed the presence of skin and cartilage. Addition of 10% MRPM to luncheon formulation could not be detected at different cooking temperatures. While the use of 30% or more MRPM to luncheon formulation, significantly changed technological properties and chemical composition of the product. Thermal treatments of luncheon sausages changed their chemical composition as well as induced structural changes in bone and cartilage content.